FUSE: A Novel Design Space Exploration Method for Aero Engine Components That Combines Functional and Physical Domains - Alejandro Pradas Gómez; Massimo Panarotto; Ola Isaksson (Aerospace)
Society awareness and environmental goals are forcing the aerospace industry to develop new sustainable system architectures. The components in the new system have to meet new functional requirements using alternative technologies and design solutions while ensuring that the physical performance of the component is maintained. However, design space exploration of both domains is challenging due to the intrinsic differences and nature of each: functional domain exploration deals with alternative means to solve functions, while physical exploration deals with parametric values, such as geometric dimensions and material types. Here, we present a method that enables concurrent exploration of the functional and physical design space. The method is based on a review of existing design space exploration methodologies. It has been developed in collaboration with industry and validated within a use case. We expect that this method will be useful for designers in conceptual phases where there are several functions containing multiple design alternatives and incompatibilities among them. The results of the method will allow designers to narrow down the design space to a few architectural candidates, including a baseline of physical dimensioning for each candidate.